IMPLEMENTASI PENDIDIKAN KASIH SAYANG DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA: STUDI KASUS DESKRIPTIF-KUALITATIF DI SDIP DARUL MUSTHOFA JAKARTA SELATAN - Cucu Cahyati; Rokimin; Hasan Darojat (Merwin Publisher, 2025)
This study aimed to: (1) analyze the urgency of loving education in developing students' discipline character; (2) describe the concept of loving education from the perspective of Prof. Arif Rachman; and (3) formulate implementation strategies for loving education in fostering student discipline at SDIP. This study employed a descriptive-qualitative design with a case study approach. The research site was purposively selected based on the following criteria: (a) an A-accredited Islamic elementary school, (b) an integrated character development program, and (c) the implementation of a loving education approach. The study was conducted over six months (June–December 2024). Informants consisted of 1 principal, 1 vice principal for curriculum affairs, 6 homeroom teachers, 10 parents, and 12 students from grades 4–6, selected through purposive sampling with inclusion criteria: teachers with a minimum of 2 years of service, parents actively involved in school activities, and students with varying levels of discipline. Data were collected through participant observation, semi-structured in-depth interviews, and documentation study. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing with verification. Data trustworthiness was ensured through source triangulation and technique triangulation. The results indicated that the integration of loving education through five main strategies empathetic communication, teacher role modeling, positive reinforcement, dialogical approach, and school–parent synergy successfully cultivated discipline based on students' internal awareness. Indicators of success were evident in: improved punctuality in attendance, compliance with school rules without direct supervision, independent task completion, and a reduction in violations requiring punitive measures.